Triathlon 2.0 data-driven performance training - Vance, Jim 1976- (Human Kinetics, 2016)
Examines the sport's most popular devices including cycling power meters, GPS trackers, and heart rate monitors. Learn to capture the most accurate readings, learn what they mean, and, just as important, what they don't mean. Learn to translate your data into a program based on your performance needs and triathlon goals.